SERVICE TYPE ANALYSIS IN PUBLIC SERVICE MALL IN JAKARTA’S INVESTMENT AND ONE-STOP INTEGRATED SERVICE (PTSP) OFFICE - Retnowati WD Tuti; Evi Satispi; Mawar Mawar; Dini Gandini dan Tria Patrianti (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Background.   Public Service Mall (PSM) is a breaktrough done by Jakarta’s Investment and One-StopIntegrated Service (PTSP) Office to improve people’s satisfaction.  Jakarta was previously known with its badpublic services conducted by local government. It’s improved up to 98% after PSM existence.  For example,Building Construction Permit (IMB) service had scattered in  various government agencies with unauthorized cost,completed in 60 days.  In reformation era, Jakarta cleaned up to prioritize the satisfaction of Jakarta’s people throughservice innovations such as one-stop integrated service IMB in PSM, Deliverance of Motor Licence (AJIB). Research Questions : 1). How  is the Forms of Service  in PSM ?; 2). What are the driving factors and innhibitors?Research Purpose , to analysis : 1).Forms of Service in PSM 2) to find out driving factors and inhibitors, ResearchFocus : 1).Forms of Services in PSM 2). IMB 3.0 and 3).AJIB . Research Methode: Descriptive; Research Approach: Qualitative; Results:  1).Forms of Service of PSM, DPM, PTSP =  292 , there are 14 Services from otherinstitutions, 2) AJIB conducted through online and offline, 3) IMB Service 3.0 free- conducted as long as it is not viabroker, will be provided free house design.  However, there are weaknesses that few people care of IMB 3.0 ; thereare many brokers; less employees; and a narrow service space.Keywords : innovation,  one-stop integrated service